Feminism in search of an identity : the Indian context - Kelkar, M. A., Mrs.; Gangavane, Deepti (Jaipur : Rawat Publications, 2003)
Contributed articles.
Identity, freedom, and empowerment / Meena Kelkar and Deepti Gangavane -- The Satapatha Brahmana on women / Nirmala Kulkarni -- Beeja-Ksetra-Nyaya : some considerations / Meena Kelkar -- Salvation and women in Jainism (with special reference to Prabhacandra Suri) / Nirmala Kulkarni -- Self-respect movement : an alternate gender discourse from below / Shantishree D.N.B. Pandit -- Man-woman relations in the writings of the saint poetesses / Vidyut Bhagwat
Includes bibliographical references and index.
Keywords: Vedic literature -- History and criticism; Philosophy, Indic; Women and religion